Dimensional reduction analyzing the thermoelastic behavior of wind turbine blades based on the variational asymptotic multiscale method. (15th December 2020) - Zheng, Shi; Yifeng, Zhong; Xiao, Peng; Peng, Wang
Highlights: A dimensional reduction model of composite wind blade is established based on VAMM. No ad hoc assumptions are involved in the derivation of the dimension reduction model. The lateral shear and normal thermoelastic stresses of realistic composite blade are correctly predicted. The details of local stress field distribution of multi-layer blade are well captured. The constructed model has the merits of high fidelity and high calculation efficiency. Abstract: Accurate and effective prediction of the thermoelastic behavior of composite wind blades is critical to the optimal design and performance evaluation. In this paper, a high-fidelity dimensional reduction model of composite wind blade is established based on the variational asymptotic multiscale method. First, the thermoelastic variational expression of 3-D composite wind blade was derived. Then, the thermoelastic energy functional was extended asymptotically to a series of 2-D energies by using the inherent small parameters of the structure, so that the original 3-D thermoelastic problem of composite wind blades was strictly divided into 2-D airfoil section analysis and 1-D beam analysis. The local displacement and stress fields were recovered based on the global response without a priori assumptions and unnecessary scale separation assumptions. Finally, the numerical examples of composite wind blades with NACA2412 airfoil and MH 104 airfoil are provided to verify the accuracy and effectiveness of the model by comparison with the three-dimensional finite element model (3D-FEM). The results show that the predicted thermoelastic behavior and local 3-D stress field of the composite wind blades are in good agreement with 3D-FEM, but the calculation efficiency is greatly improved.